COMPARISON BETWEEN THE EFFECTIVENESS OF MCKENZIE EXTENSION EXERCISES AND WILLIAM FLEXION EXERCISES FOR TREATMENT OF NON-SPECIFIC LOW BACK PAIN - Qurat-ul-Ain; Iqra ishaq (Journal of University Medical & Dental College, 2017)
ABSTRACT: BACKGROUND: Nonspecific low back pain (NSLBP) is the most common back pain and involves large population. OBJECTIVE: objective of this study was to find better treatment option between McKenzie exercises and William’s flexion exercises for non-specific low back pain. METHODS: It was a quasi-experimental study. Convenience sampling technique was used. 120 patients of both genders were included in treatment sessions. Patients with NSLBP and with age limit of 18-35 years were included in study. Visual analogue scale and revised Oswestry disability index were used to measure pain and disability. Group 1 performs McKenzie exercises and Group 2 performs William flexion exercises with each treatment session of two sets of 1015 repetitions per day. Treatment was given on 4 alternate days per week for consecutive 2 weeks. RESULTS: Independent sample t-test was applied to compare the mean VAS score of two treatment groups before treatment and after treatment. P-value for independent sample t-test (0.593) shows that there is a non-significant difference of mean VAS between two treatment groups before treatment. P-value for independent sample t-test (0.010) shows that there is a significant difference of mean VAS between two treatment groups after treatment. P-value for independent sample t-test (0.06) shows that there is a non- significant difference of mean RODI between two treatment groups before treatment. P-value for independent sample t-test (0.000) shows that there is a significant difference of mean RODI between two treatment groups after treatment. CONCLUSION: From the statistics it is clear that mean RODI is lower in McKenzie group as compare to William flexion group. McKenzie exercises greatly reduce pain and disability in patients with NSLBP. William flexion exercises also have effect on pain reduction and disability improvement but less than the effects of McKenzie exercises.